Candida Parapsilosis as a Potent Biocontrol Agent against Growth and Aflatoxin Production by Aspergillus Species - F Niknejad; F Zaini; MA Faramarzi; M Amini; P Kordbacheh; M Mahmoudi; M Safara (Tehran University of Medical Sciences, 2012)
Background: Aflatoxin contamination of food and feed stuff is a serious health problem and significant economic concerns. In the present study, the inhibitory effect of Candida parapsilosis IP1698 on mycelial growth and aflatoxin production in aflatoxigenic strains of Aspergillus species was investigated.Methods: Mycelial growth inhibitions of nine strains of aflatoxigenic and non-aflatoxigenic Aspergillus species in thepresence of C. parapsilosis investigated by pour plate technique at different pH, temperature and time of incubation.Reduction of aflatoxin was evaluated in co-cultured fungi in yeast extract sucrose broth after seven days of incubation using HPLC method. The data were analyzed by SPSS 11.5.Results: The presence of the C. parapsilosis at different pH did not affect significantly the growth rate of Aspergillus isolates. On the other hand, temperature and time of incubation showed to be significantly effective when compared to controls without C. parapsilosis (P≤0.05). In aflatoxigenic strains, minimum percentage of reductions in total aflatoxin and B1, B2, G1, G2 fractions were 92.98, 92.54, 77.48, 54.54 and 72.22 and maximum percentage ofreductions were 99.59, not detectable, 94.42, and not detectable in both G1 and G2, respectively.Conclusion: C. parapsilosis might employ as a good biocontrol agent against growth and aflatoxin production by aflatoxigenic Aspergillus species.